PREVALENCE AND FACTORS ASSOCIATED WITH THROMBOCYTOPENIA IN PREGNANCY AND ITS FETOMATERNAL OUTCOME IN A TERTIARY CARE CENTRE AT SOUTH INDIA - Dr Athira.C; Dr Rachel Alexander; Dr Meera Lekshmi Nair (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Thrombocytopenia (TCP), characterized by low platelet counts, is a haematological abnormality that occurs in approximately 5-10% of pregnancies, posing potential risks for fetomaternal outcomes. It stands as the most frequent hematological abnormality after anemia. Studies have indicated that while many instances of thrombocytopenia are mild and resolve after delivery, significant cases can lead to severe complications such as maternal hemorrhage, preterm birth, and adverse neonatal outcomesDiagnosing TCP in pregnancy is a significant concern for gynecologists due to the potential for bleeding complications during delivery. Therefore, identifying the cause of TCP is crucial, especially in antenatal patients.Aims and Objective:  The study aims to estimate the prevalence of TCP besides studying the fetomaternal outcome in antenatal women attending OPD.Materials and methods:  This prospective study enrolled 641 pregnant women and monitored them until discharge after delivery. Women with pre-existing medical conditions such as chronic liver disease, renal disorders, cardiac diseases, or malignancies were excluded from the study. During their initial antenatal visit, all participants underwent standard hematological tests, including platelet count measurements, performed using an automated blood count analyzer. Women with platelet counts below 150,000/µL were identified and closely followed up. Additionally, those with normal platelet counts before 28 weeks of gestation had a repeat test in the third trimester to screen for gestational thrombocytopenia. All cases of thrombocytopenia were tracked throughout the antenatal period and up to 48 hours postpartum to assess outcomes.Results: This prospective study consists of 641 antenatal mothers and the prevalence of TCP was 6.6%. The most common contribution was by gestational TCP, accounting for 71.4% of cases. 16.7% were due to obstetric causes, and medical causes for 12% of the cases. The incidence of still births in the TCP cases was 4.8%. NICU admission rate was 19.0%.Conclusions: Gestational TCP is the most common etiology of TCP in pregnancy and is not typically associated with any adverse outcome both for the mother or the baby. Hypertensive disorders constitute the second common etiology. ITP, SLE and APLA syndrome are rare causes of TCP in pregnancy. Although there is no risk of hemorrhagic complications in gestational thrombocytopenia as such, TCP caused by HELLP, ITP and APLA expose the mother and fetus to potentially fatal consequences which need supervision. Proper evaluation and appropriate management by both the obstetrician and hematologist place a significant role in preventing these complications.